Translational research will fail without surgical leadership: SCOTRRCC a successful surgeon-led Nationwide translational research infrastructure in renal cancer. Issue 4 (August 2015) - Stewart, Grant D.; Riddick, Antony C.P.; Rae, Frances; Marshall, Craig; MacLeod, Linda; O'Mahony, Fiach C.; Laird, Alexander; Alan McNeill, S.; O'Connor, Kevin M.; O'Donnell, Marie; Fineron, Paul; McLaren, Duncan B.; et al.
Abstract Background High quality human biosamples with associated high quality clinical data are essential for successful translational research. Despite this, the traditional approach is for the surgeon to act as a technician in the tissue collection act. Biomarker research presents multiple challenges and the field is littered with failures. Tissue quality, poor clinical information, small sample numbers and lack of validation cohorts are just a few reasons for failure. It is clear that the surgeon involved in tissue acquisition must be fully engaged in the process of biosampling for a specific condition, as this will negate many of the issues for translational research failure due to an inadequate bioresource. Approach In this Matter for Debate paper, the Scottish Collaboration On Translational Research into Renal Cell Cancer (SCOTRRCC) is discussed as an example of a urological surgery lead bioresource which has resulted in a National collection of renal cancer tissue and blood (from over 900 patients to date), negating all of the traditional issues with biobanks because of close enagagement and acknowledgement of urologists and uropathologists from seven centres around Scotland. SCOTRRCC has leveraged renal cancer research in Scotland resulting in several high impact publications and providing a springboard for future research in this disease in Scotland and beyond. Conclusions The SCOTRRCC model presented here can be transferred to other surgical disciplines for success in translational research.